Management of Warfarin Anticoagulation in Patients with Fractured Neck of Femur. (8th December 2010) - Ashouri, Feras; Al-Jundi, Wissam; Patel, Akash; Mangwani, Jitendra
Abstract : Background . Most orthopaedic units do not have a policy for reversal of anticoagulation in patients with hip fractures. The aim of this study was to examine the current practice in a district general hospital and determine difference in the time to surgery, if any, with cessation of warfarin versus cessation and treatment with vitamin K. Methods . A retrospective review of the case notes between January 2005 and December 2008 identified 1797 patients with fracture neck of femur. Fifty seven (3.2%) patients were on warfarin at the time of admission. Patients were divided into 2 groups (A and B). Group A patients (16/57; 28%) were treated with cessation of warfarin only and group B patients (41; 72%) received pharmacological therapy in addition to stopping warfarin. Time to surgery between the two groups was compared. Results . The mean INR on admission was 2.9 (range 1.7–6.5) and prior to surgery 1.4 (range 1.0–2.1). Thirty eight patients received vitamin K only and 3 patients received fresh frozen plasma and vitamin K. The average time to surgery was 4.4 days in group A and 2.4 days in group B. The difference was statistically significant (P < .01 ). Conclusion . Reversal of high INR is important to avoid significant delay in surgery. There is a need for a national policy for reversing warfarin anticoagulation in patients with hip fractures requiring surgery. Vitamin K is safe and effective for anticoagulation reversal in hip fracture patients.